Jeunes issus de l’immigration et choix d’orientation au postsecondaire à Montréal - Magnan, Marie-Odile; Pilote, Annie; Grenier, Véronique; Darchinian, Fahimeh (Canadian Journal of Higher Education, 2017)
Our qualitative interpretative research, based on a collection of life stories (n = 60), aims to better understand the experiences relating to choosing a postsecondary program of youth from immigrant backgrounds, as well as the context leading to these choices, a posteriori. The typological analysis of these life stories reveals that family plays a determining role in these choices. In addition, compared to youth from other countries, youth from sub-Saharan Africa, the Caribbean, and Central and South America perceive facing more constraints (familial, economic, and academic) when choosing their programs. They also seem to have access to fewer resources and information regarding all possible orientation choices, as well as the mechanisms and workings of the system. In conclusion, the results allow for the suggestion of intervention strategies for school staff members in order to foster the postsecondary education orientation of these youth.